Tumorigenic conversion of immortal human skin keratinocytes (HaCaT) by elevated temperature - Boukamp, Petra; Fusenig, Norbert (Oncogene, 1999)
UV-radiation is a major risk factor for non-melanoma skin cancer causing specific mutations in the p53 tumor suppressor gene and other genetic aberrations. We here propose that elevated temperature, as found in sunburn areas, may contribute to skin carcinogenesis as well. Continuous exposure of immortal human HaCaT skin keratinocytes (possessing UV-type p53 mutations) to 40°C reproducibly resulted in tumorigenic conversion and tumorigenicity was stably maintained after recultivation of the tumors. Growth at 40°C was correlated with the appearance of PARP, an enzyme activated by DNA strand breaks and the level corresponded to that seen after 5 Gy γ-radiation. Concomitantly, comparative genomic hybridization (CGH) analyis demonstrated that chromosomal gains and losses were present in cells maintained at 40°C while largely absent at 37°C. Besides individual chromosomal aberrations, all tumor-derived cells showed gain of chromosomal material on 11q with the smallest common region being 11q13.2 to q14.1. Cyclin D1, a candidate gene of that region was overexpressed in all tumor-derived cells but cyclinD1/cdk4/cdk6 kinase activity was not increased. Thus, these data demonstrate that long-term thermal stress is a potential carcinogenic factor in this relevant skin cancer model, mediating its effect through induction of genetic instability which results in selection of tumorigenic cells characterized by gain of 11q.